Efficacy of different chemicals/sterilients for the control of post-harvest rotting of betelvine leaves - R.K. CHAURASIA, R.S. NEGI and (Indian Phytopathology, 2002)
Betelvine (Piper belle Linn.) is an important cash crop for its leaves used for chewing with certain adjuncts. The betel leaves are perishable in nature and after harvest it is attacked by several diseases in. storage. Since pan is chewed raw, it is essential to use only such chemicals for control which are harmless to human health. Hence, an alternative safe method for control of post-harvest rotting of betel leaves by non-toxic chemical treatments has been tried.